Urban Poverty Among Indians In Penang: A Study On Nonmaterial Causes - S.Gopal, Parthiban (2013)
To understand urban poverty among Indians in Penang, this study sets out to explore its causes or influencing factors. It focuses on the material and more so on the non material causes as well as the extent of the impact of these causes of urban poverty among Indians in Penang. The two research sites are the Timur-laut and Seberang Perai Tengah districts. Five theories of poverty; namely theories of individual deficiencies; cultural belief; political, social and economic factors; geographical disparities and distortions and cumulative and circumstantial origins shape, guide and underpin the study. By amalgamating these theories, the issue of urban poverty is viewed from a holistic perspective. This study adopts the mixed method approach; that is utilizing both quantitative and qualitative tools to elicit data. The former consists of a questionnaire that was administered to 120 respondents while the latter comprises an in-depth interview with fifteen participants and a semi-structured interview with four stakeholders. Additionally, field notes were used to substantiate the findings. It was found that both material and non-material factors contribute to urban poverty among Indians in Penang. Furthermore, these causes are based on a multidimensional perspective, which is demonstrated by the fact that both material and non-material causes are closely interwoven although they are separate entities.